The Association of Pretreatment Systemic Immune Inflammatory Response Index (SII) and Neutrophil-to-Lymphocyte Ratio (NLR) with Lymph Node Metastasis in Patients with Papillary Thyroid Carcinoma - Gu Y; Yu M; Deng J; Lai Y (International Journal of General Medicine, 2024)
Yihua Gu, Ming Yu, Jiaqin Deng, Yeqian Lai Department of Thyroid Surgery, Meizhou People’s Hospital, Meizhou Academy of Medical Sciences, Meizhou, People’s Republic of ChinaCorrespondence: Yihua Gu, Department of Thyroid Surgery, Meizhou People’s Hospital, Meizhou Academy of Medical Sciences, No. 63 Huangtang Road, Meijiang District, Meizhou, People’s Republic of China, Email guyihuahappy@163.comObjective: Immunoinflammatory response can participate in the development of cancer. To investigate the relationship between pretreatment systemic immune inflammatory response index (SII), systemic inflammatory response index (SIRI), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR) and lymph node metastasis in patients with papillary thyroid carcinoma (PTC).Methods: A retrospective analysis was performed on 547 PTC patients treated in Meizhou People’s Hospital from January 2018 to December 2021. Clinicopathological data were collected, including gender, age, Hashimoto’s thyroiditis, maximum tumor diameter, extra-membrane infiltration, disease stage, BRAF V600E mutation, pretreatment inflammatory index levels, and lymph node metastasis. The optimal cutoff values of SII, SIRI, NLR, PLR and LMR were calculated by receiver operating characteristic (ROC) curve, and the relationship between inflammatory indexes and other clinicopathological features and lymph node metastasis was analyzed.Results: There were 303 (55.4%) PTC patients with lymph node metastasis. The levels of SII, SIRI, NLR, and PLR in patients with lymph node metastasis were significantly higher than those in patients without lymph node metastasis, while the levels of LMR were significantly lower than those in patients without lymph node metastasis (all p< 0.05). When lymph node metastasis was taken as the endpoint, the critical value of SII was 625.375, the SIRI cutoff value was 0.705, the NLR cutoff value was 1.915 (all area under the ROC curve > 0.6). The results of regression logistic analysis showed that age < 55 years old (OR: 1.626, 95% CI: 1.009– 2.623, p=0.046), maximum tumor diameter > 1cm (OR: 2.681, 95% CI: 1.819– 3.952, p< 0.001), BRAF V600E mutation (OR: 2.709, 95% CI: 1.542– 4.759, p=0.001), SII positive (≥ 625.375/< 625.375, OR: 2.663, 95% CI: 1.560– 4.546, p< 0.001), and NLR positive (≥ 1.915/< 1.915, OR: 1.808, 95% CI: 1.118– 2.923, p=0.016) were independent risk factors for lymph node metastasis of PTC.Conclusion: Age < 55 years old, maximum tumor diameter > 1cm, BRAF V600E mutation, SII positive, and NLR positive were independent risk factors for lymph node metastasis in PTC.Keywords: papillary thyroid carcinoma, lymph node metastasis, systemic immune inflammatory response index, systemic inflammatory response index, neutrophil-to-lymphocyte ratio